Sequencing Analysis of the ITS Region for Some Fusarium Species Isolated from Infected Tomato Plants - AL-Masoudi, Rasha Khalid Hussein; AL Judy, Neamat J. (Iraqi Journal of Science, 2024)
Fusarium wilt is one of the most important diseases that affects various plants and is caused by the fungus Fusarium oxysporum. Fusarium wilts in tomato plants are caused by Fusarium oxysporum f. sp. lycopersici (FOL), whether in fields or greenhouses. The tomato plant is considered one of the most important plants. This disease, however, affects its agricultural production. The current research aimed to diagnose Fusarium species that were isolated from infected tomato plants from different regions in Iraq by using molecular and morphological methods and to study the evolutionary relationship between the studied species, as twenty Fusarium isolates were obtained from infected tomato plants. Genomic DNA was amplified, using primers ITS1 and ITS4 to amplify ITS region, as there were differences between the results of the morphological diagnosis, which were based on the study of morphological features, and the molecular diagnosis which was based on the ITS region.  Depending on the morphological features, F7 and F8 isolates were diagnosed as F. oxysporum, while the molecular diagnosis of the ITS regions showed that they were F.incarnatum and F.proliferatum respectively. For the rest of the isolates, the morphological and molecular diagnoses were consistent with Fusarium oxysporum. All isolates were recorded in the Gen Bank, and were given their accession numbers. An evolutionary tree was also made for the studied isolates to know the degree of genetic convergence and divergence between them. The current study concluded that the tomato plants in the field and greenhouse from different regions in Iraq were infected with different Fusarium species, with Fusarium oxysporum f. sp. lycopersici, being the most common species, was widely spreading among the identified isolates. Conventional methods based on morphological features take time and may result in incorrect identification of closely related species. Henceforth, Fusarium species may be correctly identified by using molecular methods based on ITS sequences.